﻿Doctor's perception of clinical pharmacy services at Universitas Sumatera Utara Hospital - Khairunnisa Khairunnisa; Rima Rambe; Wiryanto Wiryanto (Pensoft Publishers, 2023)
Clinical Pharmacy Services (CPS) play important roles in the clinical setting. This study aims to evaluate CPS based on Doctors' perception at the Universitas Sumatera Utara Hospital, Medan, Indonesia. It was a mixed methods descriptive study that used the Importance-Performance Analysis (IPA). The quantitative and qualitative data were accessed simultaneously in a semi-structured interview using questionnaires as the guideline. The forty-three doctors as respondents were interviewed from October to December 2021. According to the findings, doctors have used the CPS in collaboration with clinical pharmacists in percentages ranging from 16% to 98%. Furthermore, information on drug regulatory aspects, reconciliation, and drug information services are in Quadrant II, which showed the CPS has performed well. Meanwhile, the information on pharmaceutical and clinical aspects, patient drug history, as well as recommendations and clinical pharmacy intervention, are in Quadrant III. This indicated the respondents did not consider this service to be important. Based on the interview note, increasing the capacity of CPS is important to be done.